A coumarin‐based fluorescent turn‐on probe for detection of biothiols in vitro. (29th April 2015) - Liu, Mengqiang; Jiang, Qian; Lu, Zhiyun; Huang, Yan; Tan, Yanfei; Jiang, Qing
Abstract: A novel fluorescent probe (CA‐N) was designed and synthesized for detection of biothiols. CA‐N displayed a strong fluorescence in the presence of biothiols with high sensitivity, and the mechanism for detection biothiols was based on the Michael addition reaction of a thiol group to α, β ‐unsaturated ketones. CA‐N showed low detection limit for cysteine (Cys), homocysteine (Hcy), and glutathione (GSH), which were calculated as 3.16, 0.19 and 5.15 μM, respectively. At the same time, CA‐N exhibited high selectivity toward biothiols compared with other biological amino acids. In vitro cell experiments proved that CA‐N had no cytotoxicity, high cell permeability and could be employed in living cell imaging for biothiols. Copyright © 2015 John Wiley & Sons, Ltd.